2005
DOI: 10.1103/physrevlett.94.137210
|View full text |Cite
|
Sign up to set email alerts
|

Body-Centered-Cubic Ni and Its Magnetic Properties

Abstract: The body-centered-cubic (bcc) phase of Ni, which does not exist in nature, has been achieved as a thin film on GaAs(001) at 170 K via molecular beam epitaxy. The bcc Ni is ferromagnetic with a Curie temperature of 456 K and possesses a magnetic moment of 0.52+/-0.08 micro(B)/atom. The cubic magnetocrystalline anisotropy of bcc Ni is determined to be +4.0x10(5) ergs x cm(-3), as opposed to -5.7x10(4) ergs x cm(-3) for the naturally occurring face-centered-cubic (fcc) Ni. This sharp contrast in the magnetic anis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(40 citation statements)
references
References 35 publications
2
38
0
Order By: Relevance
“…In Table 3, the experimental magnetic transition temperatures and magnetic moment of pure Fe and Ni [14,19,[54][55][56][57][58][59] are compared with the evaluation by SGTE [33] and Swartzendruber et al [39]. It was found that the recommended value of T C and b for bcc Ni by SGTE [33] needs to be revised as a result of the experiments by Tian et al [19].…”
Section: Lattice Stability Of Nimentioning
confidence: 95%
See 1 more Smart Citation
“…In Table 3, the experimental magnetic transition temperatures and magnetic moment of pure Fe and Ni [14,19,[54][55][56][57][58][59] are compared with the evaluation by SGTE [33] and Swartzendruber et al [39]. It was found that the recommended value of T C and b for bcc Ni by SGTE [33] needs to be revised as a result of the experiments by Tian et al [19].…”
Section: Lattice Stability Of Nimentioning
confidence: 95%
“…Therefore, the values of b are determined mainly from the Ni thin films, which grow on some special substrates [18,19]. For example, in the work of Tian et al [19], the magnetic moment of bcc Ni was determined from the Ni thin films by epitaxial growth on the GaAs single crystal substrate with {0 0 1} parallel to the surface. Although the experimental b in Fig.…”
Section: Experimental Datamentioning
confidence: 99%
“…Thermal stability of nanocrystals is also responsible for other thermally activated behaviors such as atomic diffusion [25,26] and crystal growth [27,28], which in turn influences the magnetic properties of nanocrystals because they depend not only on D, but on crystalline structures and presence of lattice defects [29][30][31].…”
Section: Thermal Stability Of Nanocrystalline Magnetic Materialsmentioning
confidence: 99%
“…Furthermore bcc Ni was grown successfully on Fe(001) [20][21][22] and GaAs(001) 23 . In order to gain more insight Fig.…”
Section: Methodsmentioning
confidence: 99%